FEATURES OF HSP70-2 AND HSP70-НОМ GENE POLYMORPHISM IN THE PATIENTS WITH A HISTORY OF MYOCARDIAL INFARCTION - A. V. Shevchenko; O. V. Golovanova; V. I. Konenkov; M. I. Voevoda; V. N. Maximov (Медицинская иммунология)
Аbstract.  We  have  performed  an  analysis  of  associations  between  allelic  polymorphisms  of  heat  shock protein (HSP) genes, i.e., HSP70-2 1267А→G and HSP70-НОМ 2437Т→С in Caucasian patients with acute myocardial infarction (AMI) in anamnesis, along with evaluation of common risk factors for MI. Frequency of HSP70-HOM*TC heterozygous variant proved to be significantly higher in the group with Kettle body mass index (BMI) exceeding 25, as compared with a group of relatively healthy persons. By contrary, frequency of HSP70-HOM*CC homozygosity in the MI group with BMI > 25 was significantly lower, than among healthy persons. When comparing genotype frequencies among MI patients with BMI > 25 and those with BMI<25, significance of the differences are retained, both for HSP70-HOM*TC heterozygosity and HSP70-HOM*CC homozygous state. (Med. Immunol., 2011, vol. 13, N 1, pp 87-92)